Representing Female Independence in Barbie (2023): A Feminist Semiotic Analysis - Tegar Gunawan Saputra; Asih Ernawati (Universitas Ahmad Dahlan, 2025)
The persistent dominance of patriarchal stereotypes in mainstream cinema continues to position women as passive, dependent, and limited to domestic roles, thereby marginalizing representations of female independence and leadership. In response to this phenomenon, this study aims to examine how Barbie (2023) constructs and communicates female independence through feminist ideology, using a semiotic framework. Employing a qualitative descriptive method, this research applies Saussure an and Barthes semiotic analysis to selected scenes, focusing on visual cues, symbols, costumes, settings, and narrative structures that signify empowerment and resistance to traditional gender norms. The analysis highlights women's representation in professional and male-dominated roles, such as astronauts, pilots, political leaders, and construction workers, which symbolically challenge conventional gender boundaries. The findings reveal that Barbie successfully reconciles hyper-femininity with professional competence and authority, using aesthetic elements particularly color, costume, and spatial design as ideological tools to normalize female leadership and autonomy. The novelty of this study lies in its focus on semiotic representations of liberal feminist values within a globally popular mainstream film, rather than on narrative or audience-based analysis alone. In conclusion, this research demonstrates that Barbie (2023) functions not only as entertainment but also as a cultural text that redefines femininity as independent, empowered, and capable, contributing significantly to feminist film studies and contemporary media discourse.